PEMBUKTIAN DAN PENUNTUTAN TINDAK PIDANA PERJUDIAN DENGAN MODUS GELANGGANG PERMAINAN DALAM PERSPEKTIF JAKSA SELAKU PENUNTUT UMUM DI KEJAKSAAN NEGERI PEKANBARU - Azmi Ramadhan; Erdianto Effendi; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Gambling is one of the delicts which is troubling the public. In connection with that in Article 1 of Law Number 7 of 1974 concerning the Control of Gambling reads "Declaring all gambling crimes as crimes" approved all acts of gambling crimes as crimes. But in the Criminal Code gambling has been regulated in article 303 paragraphs 1 to 3 of Law Number 27 of 1999 concerning Amendment to the Criminal Code relating to security of the State's security.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. The research was conducted at the Pekanbaru District Attorney's Office, while the population and sample were the Head of the General Crimes Section, the Head of the Prosecution Sub-Section, Gambling Criminals and Surrounding Communities. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews and literature review.The conclusions that can be obtained from the results of the study are the First, Proof and Prosecution Efforts of Gambling Criminal Acts Using the Game Arena Mode by the Public Prosecutor in the Pekanbaru District Attorney, namely the prosecutor first describes the issues and offenses relating, whether the offender is a business actor or individual to be bright in the field of proof. Secondly, Constraints and Efforts to Overcome Obstacles in Proving and Prosecuting Gambling Crimes with the Game Arena Mode in the Pekanbaru District Attorney's Office namely there are 4 factors related to gambling. Third, the Prosecutor's Step at the Pekanbaru District Attorney's Office Against the Development of Crimes Using Technology Tools, Especially in Gambling Crimes namely there are 4 things both inside and outside the court.Keywords: Gambling, Criminal Acts, Technology, Game Venues, Proof, Prosecution.